Gender Identity Minorities and workplace legislation in Europe - Katerina Sidiropoulou (Global Labor Organization (GLO), 2019)
It is a fact that transgender people experience severe discrimination in various forms not only in their everyday lives but also in their working lives, especially when transitioning. It seems that Europe is slowly changing over the years as there are constant calls to tackle this complex issue by considering the inclusion of a third gender option, the abolition of any abusive practices, recommendations for legal redress in cases of violation, and a more transparent and self-determined legal recognition procedure. There are national laws which offer protection on the basis of gender identity at national and international levels. Nevertheless, there is still a lack of uniformity due to a number of unresolved matters such as uncertainty about who is covered, whether gender identity should be covered as a protected ground, what is required to gain a legal change of name and gender marker in official documents, who is responsible for authorisation and uncertainty over the stages, nature and duration of the actual procedure. Fewer distressed transgender employees and transphobic incidents are observed when there is greater social acceptability, organisational effort and national intervention. Research and collective actions by movements, political leaders, academics, medical experts and non-governmental organisations are further required to minimise societal and employment exclusions of transgender people.
Keywords: 330; legislation; gender identity minorities; transgender employees